(untitled) (Baghdad Science Journal, 2021)
The synthesis of new substituted cobalt Phthalocyanine (CoPc) was carried out using starting materials Naphthalene-1,4,5, tetracarbonic acid dianhydride (NDI) employing dry process method. Metal oxides (MO) alloy of (60%Ni3O4 40%-Co3O4 ) have been functionalized with multiwall carbon nanotubes (F-MWCNTs) to produce (F-MWCNTs/MO) nanocomposite (E2) and mixed with CoPc to yield (F-MWCNT/CoPc/MO) (E3). These composites were investigated using different analytical and spectrophotometric methods such as 1H-NMR (0-18 ppm), FTIR spectroscopy in the range of (400-4000cm-1), powder X-rays diffraction (PXRD, 2θ o = 10-80), Raman spectroscopy (0-4000 cm-1), and UV-Visible spectrophotometry (0-800 nm). Then the activity of these materials was investigated as a gas sensing of (Ammonia, Methanol and Acetone). For each case, 0.2 mg/.mL of the prepared Copc, Copc/MWCNT, Copc/MWCNTs–MO was dispersed in 1m of ammonia, methanol and acetone at 298K. The surface morphology of the prepared materials was heterogeneous.